Coda: The last cultural capital survey?. (June 2023) - Bennett, Tony; Rowe, David
In asking whether the survey conducted for the Australian Cultural Fields project might be the last of its kind, this article reflects on the issues raised by the participants in this review symposium as well as those registered in the Fields, Capitals, Habitus book regarding the limitations of cultural capital surveys. It also draws on recent critical assessments of the degree to which the underlying principles of Bourdieu's sociology can engage adequately with the scale and character of the current escalating inequalities of class, age, race and gender. This brief analytical reflection paves the way for suggesting how cultural capital surveys might be adjusted to take account of both the issues canvassed in this symposium, as well as those needing to be addressed to engage with the inequalities that exceed the theoretical compass of the cultural capital tradition. It also acknowledges the need to reset the political compass of the forms of state action that critical cultural capital analysis proposed for reducing, if not eradicating, a range of inequalities. Despite the teasing provocation of our title, we do not finally call for cultural capital surveys to be decommissioned, but issue a challenge for them to be retooled to engage productively with new problematics and circumstances.